Impact of thermal treatment on the surface of na0.5bi0.5tio3-based ceramics - Bikse, Liga; Dunce, Marija; Birks, Eriks; Kundzins, Karlis; Freimanis, Otto; Livins, Maris; Gabrusenoks, Jevgenijs; Sternberg, Andris (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Thermal etching is a widely accepted surface treatment method for studying microstructure in Na0.5Bi0.5TiO3-based compositions. Surprisingly, besides the flat pattern of grains (suitable for evaluating ceramics’ microstructure), images illustrating well-expressed relief and even microstructure consisting of partly bonded cubic-shaped grains are also found among the micrographs presented in various publications. The present paper shows that this different surface character in Eu-modified Na0.5Bi0.5TiO3 can be obtained through thermal treatment across a wide range of temperatures. At higher temperatures, remarkable growth of cubic-shaped grains on the surface is observed. This growth affects the grain size distribution on the surface more than it does within the bulk of a sample. Such micrographs cannot be used to characterise the microstructure of dense ceramics. Intensive growth of TiO2 inclusions at high thermal treatment temperatures is also observed, revealing substantial evaporation of Bi and Na from the surface of a ceramic sample, but not from its core part. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).
This research was funded by the European Regional Development Fund, grant number 1.1.1.2/VIAA/3/19/558. The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme, grant number 739508.
Keywords: Research Subject Categories::NATURAL SCIENCES; Ceramics; Etching; Microstructure; Sodium bismuth titanate; Thermal treatment